2005
DOI: 10.1016/j.amjhyper.2005.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Intensity Resistance Training on Arterial Stiffness and Wave Reflection in Women

Abstract: We concluded that a high-intensity resistance training program increases arterial stiffness and wave reflection in young healthy women. Our present interventional results are consistent with the previous cross-sectional studies in men in which high-intensity strength training is associated with arterial stiffening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
179
4
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(203 citation statements)
references
References 13 publications
8
179
4
1
Order By: Relevance
“…Possibly, one exercise set to muscular failure may be too strenuous an intensity for reducing BP. 33 The reductions in BP found in the present study are clinically relevant, as a significant reduction in SBP of 3 mm Hg for normotensives has been shown to reduce cardiac morbidity by greater than 5%, stroke by 8-14% and all-cause mortality by 4%. 34 Thus, our data demonstrate that moderateintensity RE can be used in lieu of AE in a prehypertensive population to lower BP, and this is accomplished without weight loss.…”
Section: Discussionsupporting
confidence: 51%
“…Possibly, one exercise set to muscular failure may be too strenuous an intensity for reducing BP. 33 The reductions in BP found in the present study are clinically relevant, as a significant reduction in SBP of 3 mm Hg for normotensives has been shown to reduce cardiac morbidity by greater than 5%, stroke by 8-14% and all-cause mortality by 4%. 34 Thus, our data demonstrate that moderateintensity RE can be used in lieu of AE in a prehypertensive population to lower BP, and this is accomplished without weight loss.…”
Section: Discussionsupporting
confidence: 51%
“…24 However, high-intensity resistance training increased arterial stiffness. [10][11][12] On the basis of these results, resistance training may have to be prescribed carefully. The results of this study indicated that CRT increases arterial stiffness, whereas ERT suppresses arterial stiffness increases.…”
Section: Discussionmentioning
confidence: 99%
“…However, high-intensity resistance training reduces arterial compliance and increases arterial stiffness. [10][11][12] Muscle contractions during resistance training are performed by eccentric (ECC, lowering phase), concentric (CON, lifting phase) or isometric muscle contractions. Because ECC and CON are contraction modes accompanied by joint movement, they are widely used in typical resistance training.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of RET on AIx appear to be mixed. 9,10,[20][21][22][23] Cortez-Cooper et al 22 reported a significant increase in resting AIx after 11 weeks of high-intensity RET in young healthy women. In contrast, previous studies have shown no changes in resting AIx after RET, in young 10,20 and old, 21,23 men and women.…”
Section: Introductionmentioning
confidence: 98%